P209 What might patients mean by "Sleepiness"?. (16th November 2010) - Ghiassi, R; O'Byrne, L; Cummin, A R; Partridge, M R
Abstract : Introduction: Patients describe the symptoms of obstructive sleep apnoea syndrome (OSAS) in diverse ways. Clinicians and scientists may have difficulty in differentiating sleepiness from tiredness and tools to measure subjective or objective sleepiness do not always match clinician assessment of sleepiness. To better understand how patients' view 'sleepiness' we asked those under investigation for OSAS to describe in their own words what sleepiness means to them. Methods: 24 patients (20 male and 4 female) participated in the study. ESS scores were recorded the morning after sleep study when patients were also asked to record in their own words what sleepiness means to them. Three independent scorers, (nurse, scientist and physician) and an independent academic referee, themed answers. Participants also underwent on Oxford Sleep Resistant Test (OSLER) to quantify objective daytime sleepiness as a comparator. Results: ESS scores were grouped into the following ranges: ≤10, 11–15, 16–24 and mean OSLER scores calculated for each group, table 1 . Individually, OSLER scores did not correlate well with ESS scores and there was great variability in levels of objective daytime sleepiness. On average each patient gave 6 descriptors relating to sleepiness. Descriptors of sleepiness fell into three main categories: mental function (eg, "mugginess"), physical sensation (eg, "even moving about is exhausting") and related to sleep or actual sleep (eg, "I always fall asleep in the cinema"). Patients with an ESS: ≤10 gave more descriptors relating to physical sensations of sleepiness. Conversely patients with an ESS ≥11 gave more descriptors related to sleep or actual sleep . Conclusion: This study has begun to assess how patients using their own words, describe the symptom of 'sleepiness'. Answers fell broadly into one of three categories: mental function, physical sensation and related to or actual sleep . Further understanding the construct of sleepiness to the patient may have importance in determining who is likely to benefit from therapy with CPAP.